GEOGRAFIYA SABAQLARÍNÍŃ SÍPAT HÁM NATIYJELILIGIN TÁMIYINLEWDE KÓRGIZBELI QURALLARDÍŃ ÁHMIYETI - Nurlanov, A.S. (ILIM hám JÁMIYET, 2025)
In the article mentioned the most important periods including the youth’s coming into existence as perfect person and the increasing of the consequences of education together with upbringing affairs on some points of the secondary schools.